2021
DOI: 10.1111/jocn.16119
|View full text |Cite
|
Sign up to set email alerts
|

‘Owning the space’—person‐centred practice in a 100% single‐room acute‐care environment: an ethnographic study

Abstract: Aims and Objectives: Exploring the influence of the 100% single-room environment on staff and patient experience of person-centred practice in an acute-care setting.Background: Current building guidance for the NHS advocates increasing the singleroom inpatient environment. There is little evidence of the impact of this design in adult acute-care settings on the experience and delivery of person-centred care. Design: Ethnography, underpinned by McCormack and McCance's Person-centred Practice Framework. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
0
9
0
2
Order By: Relevance
“…Twelve studies, published between 2006 and 2022, were included in this review. Six were conducted in the United States of America (USA) (Berry & Parish, 2008; Chaudhury et al, 2006; Deitrick et al, 2010; Raj et al, 2022; Real et al, 2017; Trzpuc & Martin, 2010), three in the United Kingdom (Donetto et al, 2017; Kelly et al, 2022; Maben et al, 2016), two in Australia (Bloomer et al, 2016; Cusack et al, 2019) and one in Sweden (Rosén et al, 2017). The included studies were heterogenous in design, using various data collection approaches including survey, interview, focus groups, observation, photograph or floor plan analysis, pedometer readings and nested case study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies, published between 2006 and 2022, were included in this review. Six were conducted in the United States of America (USA) (Berry & Parish, 2008; Chaudhury et al, 2006; Deitrick et al, 2010; Raj et al, 2022; Real et al, 2017; Trzpuc & Martin, 2010), three in the United Kingdom (Donetto et al, 2017; Kelly et al, 2022; Maben et al, 2016), two in Australia (Bloomer et al, 2016; Cusack et al, 2019) and one in Sweden (Rosén et al, 2017). The included studies were heterogenous in design, using various data collection approaches including survey, interview, focus groups, observation, photograph or floor plan analysis, pedometer readings and nested case study.…”
Section: Introductionmentioning
confidence: 99%
“…In eight studies (Berry & Parish, 2008; Chaudhury et al, 2006; Cusack et al, 2019; Kelly et al, 2022; Maben et al, 2016; Raj et al, 2022; Real et al, 2017; Rosén et al, 2017), data revealed nurse participants' perspectives on the aesthetics of single rooms and their perceptions of working within the physical space, often through comparison with other unit/ward designs with multiple occupancy patient accommodation, referred to as multiple occupancy rooms. Four studies, in whole or part, provided some comparison of nurses' perspectives on single rooms compared to multiple occupancy rooms, one from the UK which used a multimethod case study approach (Maben et al, 2016), one used focus groups (Kelly et al, 2022) and two studies used surveys (Berry & Parish, 2008; Chaudhury et al, 2006). Whilst nurses in the UK study by Maben et al (2016) stated they preferred a mix of single and multiple occupancy rooms in a ward, the proximity to resources and equipment within or adjacent to each room was appreciated, as a junior sister explained:
…the gloves on the wall, just outside the general patients' room, the gloves, alcohol dispenser, aprons, and the wipes […] they're very clean, clear, easy to refill and they really benefit from being where they are, which is perfect, the fact that they're outside every single patient's room, there's no question about it.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar del incremento progresivo de miradas un tanto parciales que enfatizan este tipo de perspectivas, el reto se mantiene en llevar a la práctica los principios estables que posicionan a la persona en el centro de la atención sanitaria, con el fin de que los equipos multiprofesionales puedan ofrecer los niveles de atención adecuados y correspondientes 18 , 19 .En efecto, ninguna de las teorías particulares adopta una perspectiva verdaderamente holística que abarque la centralidad de la persona como elemento integrador de todos los agentes implicados en los procesos de salud/enfermedad (equipos sanitarios complejos y pacientes/familias/comunidades), el abordaje de sus experiencias, y su concreción en el imaginario de perspectivas personales y elementos operacionales que conjuntamente componen los complejos procesos de la atención sanitaria 20 .…”
Section: Introductionunclassified
“…El Person Centred Practice Framework (PCPF) es un marco teórico desarrollado por Brendan McCormack y Tanya McCance 21 con el deseo de operativizar el enfoque filosófico centrado en la persona, de forma que iluminara la práctica y proporcionara un lenguaje que permitiera nombrar los componentes de la persona desde una perspectiva global, así como los obstáculos y facilitadores que influyen en el desarrollo de sus potencialidades 20 . El marco PCPF 20 ayuda a los equipos multidisciplinares a entender, manejar y poner en práctica todas las dimensiones que participan en el desarrollo de una atención centrada en la persona 18 ; integra una perspectiva teórica estable y testada progresivamente a través de la investigación 2 , 19 , 21 ; y adopta un enfoque sistémico para la práctica de la atención sanitaria que opera a nivel de personas individuales, comunidades y poblaciones 21 . Se encuentra definido en la categoría conceptual de Teoría de Rango Medio 22 , por lo que articula una serie de conceptos relativamente concretos derivados de un modelo conceptual 23 , 24 , las definiciones de dichos conceptos y explicita las relaciones que se establecen entre ellos a través de las correspondientes proposiciones 25 , 26 .…”
Section: Introductionunclassified